Responsiveness of Outcome Measures in Juvenile Idiopathic Arthritis Patients Treated with Methotrexate - Islam, Mohammad Imnul; Hossain, Mahmuda; Talukder, Manik Kumar; Begum, Jesmin Ara; Rahman, Shahana A (Bangladesh Journal of Child Health, 2010)
Objective: To investigate the responsiveness of disease activity measures in juvenile idiopathic arthritis (JIA) patients treated with methotrexate (MTX) using the Standardized response median (SRM) and the effect size (ES). Design: Prospective observational study. Duration of the study was from June 2005 to December 2007. Setting: This study was carried out in the department of Paediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Participants: A total of 58 consecutive patients were enrolled in the study but 40 patients completed their regular follow-up. All patients received MTX orally along with non-steroidal anti-inflammatory drugs (NSAID) and/or steroid. Results: The subjective variables including physician's and parent's global assessment were most responsive instrument. Among the articular variables, number of joints with limited range of motion was the most responsive. Functional ability was the lowest responsive. Conclusion: While SRM and ES had been used to evaluate the responsiveness, the physician's and parent's global assessment and number of joints with limited range of motion were the most responsive outcome measure in the therapeutic response in JIA patients. Keywords: Standardized response median (SRM); effect size (ES); responsiveness. DOI: 10.3329/bjch.v32i1.5992 Bangladesh Journal of Child Health 2008; Vol.32(1): 1-5